Diagnostic capabilities of transcranial magnetic stimulation to predict motor recovery after a stroke - M. A. Nazarova; P. A. Novikov; V. V. Nikulin; G. E. Ivanova (Нервно-мышечные болезни, 2020)
Transcranial magnetic stimulation is a method of focal non-invasive brain stimulation, characterized by high spatial and temporal resolution. To date, diagnostic transcranial magnetic stimulation has been used in clinical practice primarily to assess an involvement of the upper motor neurons and to measure the velocity of the neuronal impulse propagation. However, in the last 10 years, a possible range of transcranial magnetic stimulation diagnostic applications has significantly expanded. Many transcranial magnetic stimulation approaches are coming from scientific laboratories to clinical practice due to an increased availability of transcranial magnetic stimulation equipment, in particular, magnetic resonance imaging navigation for transcranial magnetic stimulation and a combination of the transcranial magnetic stimulation with electroencephalography and also due to an increased awareness of the clinicians. The diagnostic potential of transcranial magnetic stimulation in relation to motor recovery after a stroke can be classified into 4 directions:1) assessment of the vertical tracts integrity (primarily, the cortico-spinal tract); 2) an assessment of the cortical excitation-inhibition balance;3) probing of the functional and effective connectivity among brain regions (primarily, cortical convexity and cerebellum);4) motor mapping to evaluate cortical reorganization.In this article we will present these 4 directions of the transcranial magnetic stimulation application to study motor system pathophysiology and to predict motor outcome in stroke, including both existing and developing approaches.